Tinjauan Naratif tentang Hubungan Asupan Kalsium terhadap Hipertensi pada Kehamilan - Rezzita Astiani; Mona Nulanda; Amelia Abdullah (2026)
Hypertension in pregnancy is one of the leading causes of maternal morbidity and mortality worldwide. One potential preventive approach is adequate calcium intake during pregnancy. Objective: To review the relationship between calcium intake and the incidence of hypertension in pregnancy through a recent literature review. Methods: This study is a narrative review of 10 scientific articles published in 2020-2025, with searches through Google Scholar, PubMed, and other databases using the keywords “calcium”, ‘hypertension’, and “pregnancy”. Results: Most articles (9 out of 10) showed a significant association between calcium intake and reduced risk of hypertension in pregnancy. Conclusion: Adequate calcium intake plays an important role in reducing the risk of pregnancy hypertension. Other factors such as maternal age, nutritional status, and sodium intake also need to be considered in prevention efforts.